Alcohol expectancies and drinking behaviors among college students with disordered eating. Issue 3 (2nd April 2016) - Rush, Christina C.; Curry, John F.; Looney, John G.
ABSTRACT: Objective : The authors investigated binge drinking, alcohol expectancies, and risky and protective drinking behaviors in relation to disordered eating behaviors in male and female college students.Participants : The full sample consisted of 7, 720 undergraduate students, 18 to 22 years of age. Drinking behaviors were analyzed in 4, 592 recent drinkers.Methods : Participants anonymously completed a survey as part of a universal alcohol abuse prevention program between September 2007 and April 2008.Results : Co-occurring disordered eating behaviors and binge drinking characterized 17.1% of males and 19.0% of females. Rates of binge drinking were higher in those with disordered eating behaviors. Students with disordered eating behaviors also had more positive and negative alcohol expectancies and engaged in more risky and fewer protective drinking behaviors than their counterparts.Conclusions : Students with disordered eating behaviors have outcome expectancies and behavior patterns associated with problematic drinking. These findings may enhance prevention and intervention programs.